An enquiry into the role of classroom management in enhancing learners’ social skills - Ahmed, Nadeem (Journal of Management and Business Education, 2024)
Learners’ social skills enhancement is one of the key components of the classroom and the basic obligation of a teacher and school. Thus, it is imperative to manage the classroom in a way that can offer a comfortable teaching-learning environment to learners. Therefore, the study aimed to examine to role of classroom management in enhancing learners' social skills. The interpretive research design was utilized to describe the qualitative data, and a generic qualitative research approach was employed to undertake the study. A total of 18 teachers from six secondary schools were selected by using a purposive sampling technique. It was instituted that classroom management and the social environment of the classroom play a vital role in learners' social skills enhancement. Based on research findings, physical resources, teacher role, class rule, conduct and regulation, socioeconomic status of learners, family background, and poverty are the leading factors that have a strapping role on learners’ skills enhancement. The selected schools to accomplish research are lacking resources, however, teachers are considered as a core in teaching-learning. It is, therefore, obligatory to provide resources to classrooms, skills to teachers, and address learners' socioeconomic status to achieve educational goals and enhance social skills.